MODIFYING PROCESSUALITY OF EMOTIONS OF A MUSICIAN-PERFORMER - ZAIETS, Vitalii; ZAIETS, Oksana (Studia Universitatis Babes-Bolyai Musica, 2023)
The essence of this research is to understand the professional and creative specifics of the emotional thinking of a musician-performer. The idea arose from the experience of performing activities, teaching and scientific research in the context of the traditions of performing arts and the theoretical opinion of experts in the field of musicology. The main task consists in substantiating the methodological and theoretical principles, methods of approach to determining the functional features of the emotional tone of a musician-performer as a tool for the formation of professional thinking of a creative personality. In such formulation of the question, it is necessary to proceed from the fact that the problem of human thinking is generally constantly active, meaning that it is in a procedural state as both, an individual person and his/her natural environment, assimilate and generate new emotions (feelings), and, therefore, directly carry out influence on the flow of mental processes. The processuality of this dual dynamic psychological modification is endless, and the disclosure of regularities here also has a timely processual and continuously renewed character.